Pola Pemahaman Keagamaan Islam Pada Narapidana Anak Di Lembaga Pemasyarakatan Kelas I Medan - Utami, Fadillah; Zulkarnain (Kartika: Jurnal Studi Keislaman, 2025)
The pattern of Islamic religious understanding formed in prisons often differs from that which develops in the general community. Outside of prisons, religious understanding is influenced by tradition, family environment, and open access to religious education. Inside prisons, religious understanding is shaped through formal and structured guidance programs. The purpose of this study is to describe the patterns of religious understanding among juvenile inmates at the Class I Prison in Medan and to what extent the rehabilitation programs implemented can bring about changes in their religious understanding and attitudes. This study employs a qualitative research method. It was found that after participating in the rehabilitation programs, there was an increase in religious awareness and practice.